Does Patient-Centered Attitude Improve During Internship? A Longitudinal Study - Ali Akbar Rohani; Reyhaneh Ebrahimi; Habibeh Ahmadipour (Kerman University of Medical Sciences, 2019)
Background The patient-centered approach improves the quality of health care. Promoting this approach will increase the patients' satisfaction and improve interpersonal skills among health care providers. Objectives The aim of the current study was to compare the viewpoints of interns toward the patient-centered approach in the beginning and the end of the internship at the Kerman University of Medical Sciences (KUMS). Methods This longitudinal study was carried out at KUMS between March 2017 and July 2018. All medical students who had passed the internship entrance exam were selected through a census. The Persian version of the patient-practitioner orientation scale (PPOS) was completed at the start and the end of the internship. This instrument has 18 items in two 9-item subscales: sharing and caring. The minimum and maximum scores were 1 to 6, respectively. The higher the score, the more the patient-centered orientation. The data were analyzed by SPSS using independent and paired -tests, ANOVA, and multiple linear regression. Results The mean scores of PPOS were 3.92 ± 0.42 and 3.86 ± 0.37 at the beginning and the end of the internship, respectively. This difference was not statistically significant. The mean score of the caring subscale significantly increased during internship but no significant change was found in the mean score of the sharing subscale. Conclusions The results of our study showed that the patient-centered attitude toward patient caring improved during the internship in the majority of interns but no significant improvement was found in terms of patient sharing. Significant progress can be made in the quality of physician-patient communication and patient satisfaction if necessary training programs are run on patient-centeredness.